AUDIT ENERGI LISTRIK PADA GEDUNG PLASA TELKOM TEUKU UMAR DENPASAR - Ayu Rahmawati; I Made Suartika; Ida Bagus Gede Manuaba (Jurnal SPEKTRUM, 2021)
The increasing need for electrical energy every year results in the availability of energysources is dwindling. Therefore, the need for energy conservation to streamline the use ofelectrical energy without reducing its comfort or productivity. The main factor of energyconservation is energy auditing. Plasa Telkom Teuku Umar is a company engaged intelecommunications. The convenience of employees and customers takes precedence overthis0company.0The best service0must also be followed by the efficient use of facilities. For thisreason, an electrical energy audit is needed. In this study, it was attached0to theair0conditioning0system and lighting system. It is attached to the air conditioning system andlighting system. Tools0that can be0used for measurement in the field are Lux Meter, (lightintensity measurement), Tang Ampere (electric current measurement), and Thermometer (roomtemperature measurement). The study was conducted by0calculating and comparing0electricalenergy consumption in lighting and air conditioning systems between before and after anenergy audit. Calculate the pre- and post-audit IKE (Energy Consumption Intensity) andcompare it to the IKE standard. The results of the study found energy savings of 36.06%. Fromelectricity usage of 16.86 kWh/m2/bln pre audit to 10.78 kWh/m2/mo post audit.